Factor VII Activity Is an Independent Predictor of Cardiovascular Mortality in Elderly Women of a Sicilian Population: Results of an 11-year Follow-up - Noto, D.; Barbagallo, C. M.; Cefalu, A. B.; Cavera, G.; Sapienza, M.; Notarbartolo, A.; Davi’, G.; Averna, M. R. (Thrombosis and Haemostasis, 2002)
The aim of the Epidemiological project “Ventimiglia di Sicilia” is to identify the cardiovascular risk factors in a Sicilian population with a low risk profile and healthy nutritional habits. The risk of cardiovascular mortality in older subjects (over 60 years of age) is presented for an 11 year follow-up. Females showed higher prevalence of diabetes mellitus, hypertension, obesity and higher levels of total, LDL and HDL cholesterol, factor VII activity and fibrinogen compared to males. Cardiovascular mortality was related to hypertension and obesity in males, to high factor VII activity, obesity and diabetes mellitus in females. In a Logistic Regression model the same variables were independently correlated to cardiovascular mortality with the exception of obesity. In conclusion, these findings suggest that in a population with a low risk profile, other factors, such as factor VII activity, may emerge as predictors of cardiovascular mortality.
Keywords: Epidemiology; cardiovascular disease; coagulation; lipoproteins; factor VII activity